ETYMOLOGICAL AND CULTURAL INTERPRETATION OF COLOR IDIOMS IN ENGLISH AND UZBEK (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the semantic and cultural dimensions of color idioms in both English and Uzbek languages. Color idioms are fixed expressions that include color terms and convey figurative meanings, often rooted in historical, emotional, and societal connotations. The study aims to identify similarities and differences between English and Uzbek color idioms, tracing their etymological roots and cultural symbolism. The paper reveals that while some color idioms show universal meanings (such as “white” symbolizing purity), many others are deeply culturespecific. Through comparative analysis, this research enhances understanding of how colors metaphorically reflect human emotions, values, and worldview in two distinct linguistic and cultural contexts.